Oral squamous cell carcinoma with lung and kidney metastases in a hoary fox (Lycalopex vetulus) - Zanoti, Isabela Coelho; Gouveia, Bethânia Almeida; Ramos, Fernanda Ramalho; Klein, Mariana [UNESP]; Momo, Claudia (Brazilian Journal of Veterinary Pathology, 2024)
Oral squamous cell carcinoma is a common malignant tumor of epithelial cells in dogs. This tumor metastasizes slowly and primarily affects the gingiva. Despite its importance, few studies document this cancer in wild canids. A young adult female hoary fox (Lycalopex vetulus) kept in captivity at Associação Mata Ciliar (Jundiaí, SP, Brazil) exhibited clinical signs such as weakness, prostration, and severe oral bleeding. After anesthetizing the animal, a reddish, friable verrucous formation was observed on the upper and lower lip, as well as on the maxillary and mandibular gingiva on the right side of the mouth, extending towards the bony palate. A biopsy of this mass was performed, followed by histopathological and immunohistochemical evaluation. Histopathology indicated an atypical squamous proliferation with inflammatory features suggestive of poorly differentiated squamous cell carcinoma, which was confirmed by immunohistochemistry through the positive expression of antibodies AE1AE3, p63, and CK14. The proliferation marker ki67 was used to assess the aggressiveness and malignancy of the tumor, and it was found in approximately 80% of the neoplastic cells. Because of the poor prognosis, the hoary fox was euthanized, and a necropsy was performed. Histopathological analysis of the tissues revealed lung metastasis, suppurative bronchopneumonia, and renal metastasis associated with neutrophilic interstitial nephritis and tubular necrosis. The present report describes this type of neoplasm for the first time in a hoary fox and one of the few observed in wild canids. The scarcity of research on neoplasm incidence in wild canids in Brazil emphasizes the need for further investigations to understand tumor development in these species better.
Keywords: canids; neoplasm; pathology; wildlife disease